A systematic review of chyle leaks and their management following axillary surgery. Issue 6 (June 2020) - Farkas, N.; Wong, J.; Monib, S.; Thomson, S.
Abstract: Introduction: Chyle leaks following surgery to the axilla are seldom encountered with an incidence <0.7%. Management varies with no consensus in the literature. Injury to branching tributaries of the thoracic duct may require lengthy management at significant cost to patient and clinical team. This paper aims to provide an up-to-date review to support clinical management. Methods: The term 'chyle' was combined with 'breast' or 'axilla.' EMBASE, Medline and PubMed database searches were conducted. All papers published in English were included with no exclusion date limits. Results: 51 cases from 31 papers. All were female (mean age = 53.3yrs). 47/51 leaks were left-sided. 5/51 underwent sentinel node biopsy, 19/51 level II axillary node clearance (ANC), 23/51 level III ANC, 5/51 not specified. 59% (30/51) of leaks were identified within 2 postoperative days (mean = 3.3days). 96% initially managed conservatively: Drain = 38/51; low-fat diet = 34/51; compression bandaging = 20/51; Aspiration = 6/51. 40/51 (78%) were successfully managed conservatively, 11 patients returned to theater for secondary management. 7/11 recorded volumes >500mls/24 hrs before secondary surgery. Mean resolution time from initial surgery was 17.3days (range = 4–64days). No statistically significant difference (p = 0.72) in time to resolution between conservatively and surgically managed patients. Conclusions: Chyle leaks are rarely seen following axillary surgery. Aberrant thoracic duct anatomy represents the likeliest aetiology. We advocate early recognition and tailored individual management. Conservative management with non-suction drainage, low-fat diet and axillary compression bandaging appear effective where output <500ml/24 hrs. Secondary surgical management should be considered in high chylous output (<500mls/24 hrs) patients unresponsive to conservative measures. We propose a management algorithm to aide clinicians.